Improving rate capabilities of hybrid supercapacitor using Li4Ti5-xZrxO12/activated carbon - 이승환; 정태훈; 남성필; 임인호 (Journal of ceramic processing research, 2016)
The Li4Ti5-xZrxO12 (x = 0, 0.15, 0.3, 0.45 and 0.6) anodes were prepared using a simple solid-state method. We investigated theelectrochemical performance of hybrid supercapacitor using Zr4+ doped Li4Ti5O12 anode and activated carbon cathode. WhenZr entered Li4Ti5O12, the higher lattice parameters and conductivities of Li4Ti5-xZrxO12 (x = 0.15, 0.3, and 0.45) obviouslyimproved the electrochemical performance of hybrid supercapacitor. Among them, the Li4Ti4.55Zr0.45O12 anode has a superiorspecific capacitance of 69 Fg−1at 0.5 Ag−1rates. Also, the power and energy densities were 212.3 W kg−1and 65.2 Wh kg−1,respectively. KCI Citation Count: 2